Significance of Molten Hydroxides With or Without Molten Carbonates in High-Temperature Electrochemical Devices - Gürbüz, Ersan; Grépin, Elisa; Ringuedé, Armelle; Lair, Virginie; Cassir, Michel (Frontiers in Energy Research, 2021)
Due to their low melting point and high conductivity molten hydroxides are interesting electrolytes, or additive to other molten electrolytes for high-temperature electrochemical devices. There is nowadays a revival of such reactive media, first of all for their significant role in the electrode mechanisms in molten carbonate fuel cells (MCFCs) and the reverse co-electrolysis of water and carbon dioxide process, but also in different applications, among which direct carbon fuel cells (DCFCs), hybrid carbonate/oxide fuel cells. This overview shows the properties and interest of molten hydroxides and their use in relevant energy devices, pointing out their direct use as electrolytic media or as key species in complex kinetic processes. A thorough understanding of their behavior should allow improving and optimizing significantly fuel cells, electrolyzers, and probably also CO2 capture and valorization.